Rhetorical Culture and Brand Slogan: An Analysis of the Slogans of all Commercial Banks from Nepal - Lamichhane, Yog Raj (Journal of Nepalese Business Studies, 2021)
Rhetoric is the artful deviation of information and ideas. It is commonly utilized in different forms of advertising. In this context, the study has examined how rhetorical devices are employed in the brand slogans of the 28 commercial banks in Nepal. To achieve their dominant theme there, it identifies and categorizes the devices following the taxonomy developed by James H. Leigh. The framework divides such figures of speech into 41 types under 2 major categories schemes and tropes. The finding from this descriptive analysis and has indicated that music, memory, association, emphasis, emotion and exaggeration are some popular constructs for designing the slogans. Moreover, Nepali private commercial banks seem more successful in utilizing such strategies as they have applied maximum rhetorical devices in comparison to foreign joint -venture and governmental banks. In this trajectory, foreign joint-venture banks have an international brand in the name itself, governmental banks can communicate with customers being people's banks and private banks appear smart in incorporating maximum wordplays in the slogans to play with the sentiment of the audience influencing them. The study simultaneously contributes to both the fields of creative writing and marketing communication literary world and marketing sector updating the current awareness about rhetorical culture. The study has only included the slogans of commercial banks from Nepal, but the comparative study between the slogans of all the banks from Nepal and the banks' slogans from other countries may reflect a clearer picture regarding rhetorical culture.